SINERGITAS STAKEHOLDER DALAM PENGEMBANGAN OBJEK WISATA PANTAI PURWAHAMBA INDAH KABUPATEN TEGAL - Putri Rosiana Dewi,; Ida Hayu Dwimawanti; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
To realize successful tourism development requires synergy between the stakeholders involved. Likewise in the development of tourist objects Purwahamba Indah Beach which is located in Tegal Regency. Stakeholders for the development of the Purwahamba Indah Beach tourism object are the Tegal Regency Disporapar, PT BPK, and Pokdarwis Pesona Bahari. The success of the synergy between stakeholders can be seen through the communication and coordination of tourism activities. The purpose of this study is to describe and analyze the success of stakeholder synergy and the factors that hinder the realization of stakeholder synergy in the development of Purwahamba Indah Beach tourism objects. The method used in this research is descriptive qualitative method. The results of the study show that stakeholders in the development of Purwahamba Indah Beach attractions have not yet synergized. Communication and coordination between stakeholders is not optimal. Stakeholders have not carried out their roles properly as stated in the Regional Regulation of Tegal Regency No. 7 of 2018. Disporapar involvement is still not optimal. The unrealized hopes of developing Purwahamba Indah Beach with the conditions on the ground led to a decline in trust between stakeholders involved in the development of Purwahamba Indah Beach. Disporapar's responses tend to be less good at dealing with infrastructure problems that have decreased feasibility and lack of maintenance has an impact on direct relationships and weakened stakeholder participation. To encourage the realization of synergy between stakeholders, a special evaluation is needed to increase professionalism between stakeholders in the development of the Purwahamba Indah Beach tourist attraction, Tegal Regency